2021
DOI: 10.4103/joacp.joacp_338_17
|View full text |Cite
|
Sign up to set email alerts
|

High-volume, multilevel local anesthetics–Epinephrine infiltration in kyphoscoliosis surgery

Abstract: Background and Aims: Local anesthetic (LA) infiltration is one of the analgesic techniques employed during scoliosis correction surgery. However, its efficacy is controversial. In the present study for optimizing analgesia using the infiltration technique, we proposed two modifications; first is the preemptive use of high volume infiltration, second is applying three anatomical multilevel infiltrations involving the sensory, motor, and sympathetic innervations consecutively. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…LA infiltration by a surgeon before wound closure is a quick and inexpensive way to provide pain relief. In some spine surgery studies, it has been shown to be effective, 70,71 but a definite conclusion cannot be drawn due to heterogeneity and a lack of robust data 72 . In recent studies, PNBs have outshone LA infiltration in this matter 73,74 .…”
Section: Enhanced Recovery After Surgery and Multimodal Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…LA infiltration by a surgeon before wound closure is a quick and inexpensive way to provide pain relief. In some spine surgery studies, it has been shown to be effective, 70,71 but a definite conclusion cannot be drawn due to heterogeneity and a lack of robust data 72 . In recent studies, PNBs have outshone LA infiltration in this matter 73,74 .…”
Section: Enhanced Recovery After Surgery and Multimodal Analgesiamentioning
confidence: 99%
“…Erector spinae plane block [47][48][49][50][51][52][53] Most studied block in adult spine surgeries Associated with reduced opioid consumption intraoperatively and postoperatively, lower pain scores, less NV and better patient satisfaction More comparative effectiveness studies are required Most studied block in pediatric spine surgeries Associated with reduced opioid consumption intraoperatively and postoperatively, lower pain scores, less NV and better patient satisfaction More comparative effectiveness studies are required Thoracolumbar interfascial plane block [56][57][58][59] Limited studies with mixed results Not studied Midpoint transverse process to pleura block 45,46 Inadequate data Not studied Quadratus lumborum block 60 Single retrospective study Can be used for anterior and posterior approach lumbar spine surgeries Not studied Surgical infiltration [67][68][69][70][71][72][73][74]…”
Section: Not Studiedmentioning
confidence: 99%